2022
DOI: 10.1037/edu0000671
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive appraisals, achievement emotions, and students’ math achievement: A longitudinal analysis.

Abstract: Based on control-value theory (CVT), we examined longitudinal relations between students’ control and value appraisals, three activity-related achievement emotions (enjoyment, anger, and boredom), and math achievement (N = 1,716 fifth and seventh grade students). We assessed appraisals and emotions with self-report measures of perceived competence in math, perceived value of math, and math emotions, and achievement with school grades in math. All variables were measured in each of three consecutive annual asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 106 publications
6
56
1
Order By: Relevance
“…However, achievement outcomes also reciprocally influence students’ emotions. Specifically, CVT proposes that success and failure shape students’ perceptions of control over achievement, such as their competence beliefs and expectancies of success, and may also influence the perceived value of achievement (Forsblom et al, 2021). As outlined above, perceived control and value are proximal antecedents of achievement emotions.…”
Section: Achievement Emotionsmentioning
confidence: 99%
“…However, achievement outcomes also reciprocally influence students’ emotions. Specifically, CVT proposes that success and failure shape students’ perceptions of control over achievement, such as their competence beliefs and expectancies of success, and may also influence the perceived value of achievement (Forsblom et al, 2021). As outlined above, perceived control and value are proximal antecedents of achievement emotions.…”
Section: Achievement Emotionsmentioning
confidence: 99%
“…It is thus questionable whether frequent relief is desirable, especially when considering that, as in prior research (e.g., Pekrun et al 2011), it was the only positive AE that, like all negative AEs examined, was negatively related to achievement. Of note, the lack of systematic relations between other positive AEs (i.e., enjoyment, hope, pride) and training needs seems surprising considering that evidence points to positive effects of these emotions on students' learning and academic performance (Forsblom et al 2021;Pekrun 2018). In light of these patterns, it is important to emphasize that the present data may at least in part be shaped by students' beliefs about the functions of specific AEs for learning.…”
Section: Training Needmentioning
confidence: 65%
“…Moreover, programs targeting students' social-emotional learning (SEL) emphasize broader life skills, positive youth development, and social skills, but lack components addressing the regulation, determinants, and outcomes of AEs (Goetz et al 2005). As effective regulation of emotions is person-, emotion-, and context-specific (i.e., contingent upon situational demands and personal resources; Aldao et al 2015), and the experience as well as regulation of positive and negative emotions largely independent (Green & Salovey, 1999) equipping students with skills for combatting different negative AEs, and for increasing positive AEs that have been found to boost learning and performance (Pekrun 2018; see also Forsblom et al 2021; for recent evidence in secondary education contexts), is an important line of inquiry for education scholars that can complement and broaden the scope of extant SEL programs. This inquiry should take students' needs and preferences into account from early stages of program development onwards, and for determining implementation conditions.…”
Section: Frequencies and Functions Of Achievement Emotionsmentioning
confidence: 99%
“…In the context of higher education, there is already evidence for the relevance of achievement emotions in educational contexts prior to scientific careers of doctoral graduates (e.g., undergraduate degree programs) (Pekrun and Stephens, 2010). Furthermore, emotional experiences are relevant for academic achievement and progress: previous studies provided evidence for the impact of achievement emotions on various factors such as achievement (Staw et al, 1994;Weiss and Cropanzano, 1996;Pekrun, 2006;Peixoto et al, 2016;Pekrun et al, 2017;Shao et al, 2020;Forsblom et al, 2021), motivation (Pekrun, 2006;Vandercammen et al, 2014;Løvoll et al, 2017), and well-being (Deci and Ryan, 2000;Pekrun, 2006). Achievement, motivation and well-being resulting from positive emotional experiences can be assumed as basis for scientific progress because only motivated, mentally healthy researchers are able to make scientific achievements and to contribute to scientific progress.…”
Section: Emotional Experiences In Academiamentioning
confidence: 99%
“…Tran et al (2021) concluded that evaluating the emotional state is relevant for estimating general well-being of academic staff and for preventing burnout (Tran et al, 2021). Furthermore, there is empirical evidence that emotions are important drivers for many psychological aspects related to scientific success, such as motivation (e.g., Løvoll et al, 2017), well-being (e.g., Pekrun, 2006), and academic achievement (e.g., Pekrun et al, 2017;Forsblom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%